Eco-friendly silver nanoparticles (AgNPs) fabricated by green synthesis using Capsicum annum L. extract: biosynthesis, characterization, and antibacterial activity - Erna Fitriany Fitriany; Andri Priyoherianto; Panji Ratih Suci (University of Bengkulu, 2023)
Silver nanoparticles (AgNPs) have many benefits in the health sector, it has antimicrobial and biomedical Activity. AgNPs can be synthesized by using green chemistry or using chemical substances, such as NaBH4. Green synthesis of AgNPs is an environmentally friendly alternative and has cost-effective production. Capsicum annuum L. combined with Saffron extract was used to synthesize AgNPs. The biosynthesis, characterization, and antibacterial activity of AgNPs were studied in this research. The synthesized AgNPs were characterized by UV- Visible spectroscopy (UV-Vis), Fourier- transform Infrared Spectroscopy (FTIR), and Particle Size Analyzer (PSA). The formation of AgNPs was confirmed by optical performance using UV-VIS spectroscopy and showing a peak of AgNPs at 407 nm. Capsicum Annuum L. combined with Saffron extract contained C-H, C-N, and C=O groups. The particle size was characterized using PSA, the size is 37,74 nm. Capsicum Annuum L. combined with Saffron extract has good antibacterial activity. Keywords: Green Synthesis, AgNPs, Capsicum annuum L, Saffron.